Carbapenem-resistant bacteria in an intensive care unit: prevalence and associated factors (Research, Society and Development, 2022)
Antimicrobial resistance is a global threat that requires different care and factors involved including a unified, multidimensional approach, with greater epidemiological surveillance. The objective this study was to review the prevalence and factors associated with healthcare-related infections (HAI) caused by bacteria resistant to carbapenems in adult patients admitted to the Intensive Care Unit (ICU). This was a cross-sectional study accomplished through the review of electronic medical records and microbiological tests of patients admitted to the ICU of a hospital in southern Santa Catarina between 2010 and 2017. Demographic, clinical and antimicrobial use data were part of the variables of interest. A total of 1,273 HAI cases were included, 11.5% of the hospital infection rate. The mean age of patients was 60.4±18.5 years; 58.7% of the patients were men. The main cause of hospitalization was cardiac-related diseases (35.8%) and the median hospital stay was 31 days. Of the total number of cases, 24% were due to carbapenem resistance. HAIs caused by Escherichia coli, coagulase-negative Staphylococcus/Staphylococcus aureus and Streptococcus sp. were the pathogens that showed greater resistance to carbapenems. Resistance to carbapenems was associated with longer hospital stay (p=0.014), surgical procedure (p